2020
DOI: 10.1186/s13041-020-00656-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 facilitates inflammasome activation via epigenetic suppression of Nrf2 in Parkinson’s disease

Abstract: The goal of the present study was to elucidate the mechanism by which long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) promotes inflammation in Parkinson’s disease (PD). 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) was used to induce PD development in C57BL/6 mice, and tyrosine hydroxylase (TH) expression was analysed by immunohistochemical analysis. Western blot and qPCR analyses were conducted to assess the expression of protein and mRNA levels, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 45 publications
0
64
0
Order By: Relevance
“…Besides, Liu et al indicated that MALAT1 promoted the apoptosis by sponging miR-124 in mouse models of PD and in vitro model of PD [ 33 ]. Cai et al showed that MALAT1 could induce inflammasome activation and reactive oxygen species (ROS) production in PD mouse and microglial cell models by epigenetically inhibiting NRF2 [ 34 ]. Consistent with previous research, in our study, MALAT1 depletion rescued the decreased cell proliferation and increased apoptosis in MPP + -treated SK-N-BE and SK-N-BE cells, indicating the pivotal role of MALAT1 in the apoptosis of neurons in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Liu et al indicated that MALAT1 promoted the apoptosis by sponging miR-124 in mouse models of PD and in vitro model of PD [ 33 ]. Cai et al showed that MALAT1 could induce inflammasome activation and reactive oxygen species (ROS) production in PD mouse and microglial cell models by epigenetically inhibiting NRF2 [ 34 ]. Consistent with previous research, in our study, MALAT1 depletion rescued the decreased cell proliferation and increased apoptosis in MPP + -treated SK-N-BE and SK-N-BE cells, indicating the pivotal role of MALAT1 in the apoptosis of neurons in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that lncRNAs are involved in regulating neuroinflammation, oxidative stress (Cai et al, 2020), apoptosis (Zhang et al, 2020), and autophagy (Yan et al, 2018) that are related to the pathogenesis of PD. Differentially expressed lncRNAs were identified in the circulating leukocytes of patients with PD as well as healthy subjects (Fan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, long ncRNAs (lncRNAs) have major roles in NDDs. Cai et al [ 162 ] have demonstrated that long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1(lncRNA MALAT1) epigenetically suppresses the expression of Nrf2 and triggers inflammatory response in PD mice and BV-2 cells. A novel lncRNA termed Nostrill is highly expressed in LPS-stimulated microglia cells with concomitant increased expression of iNOS.…”
Section: Epigenetic Regulation Of Microglia Function and Phenotypes In Neurodegenerative Diseasesmentioning
confidence: 99%